The evolving epidemiology of valvular aortic stenosis. The Tromsø Study - Eveborn, Gry Wisthus; Schirmer, Henrik; Heggelund, Geir; Lunde, Per; Rasmussen, Knut (Heart (British Cardiac Society), 2013)
Objective To assess prevalence, incidence, prognosis and progression of degenerative valvular aortic stenosis (AS). Setting The Tromsø Study and the University Hospital of North Norway. Design Population based prospective study. Population Over a 14 year span we performed three repeated echocardiographic examinations (1994, 2001 and 2008) of a random sample of initially 3273 participants. Data from the only hospital serving this population were included. Results There were 164 subjects with AS. Prevalence consistently increased with age, average values being 0.2% in the 50–59 year cohort, 1.3% in the 60–69 year cohort, 3.9% in the 70–79 year cohort and 9.8% in the 80–89 year cohort. The incidence rate in the study was 4.9‰/year. The mean annual increase in mean transvalvular pressure gradient was 3.2 mm Hg. The increase was lower in mild AS than in more severe disease, disclosing a non-linear development of the gradient, but with large individual variations. Mortality was not significantly increased in the asymptomatic AS-group (HR=1.28), nor in those who received aortic valve replacement (n=34, HR=0.93), compared with the general population. Conclusion This is the first study to document the incidence and prognosis of AS in a general population with surgery as a treatment option. It reveals an accelerated progression of the aortic mean gradient as the disease advances. The prognosis of AS seems to be comparable with the normal population in the asymptomatic stage and after successful surgery, indicating that the follow-up and timing of surgery has been adequate for this patient group.